The moderating role of gender in the effects of an exercise and nutrition intervention module on body composition and fitness profiles among obese college students - Ning, Wang; Cheah, Mun Hong Joseph; Yit, Siew Chin; Appukutty, Mahenderan (Richtmann Publishing, 2024)
Introduction: This study explores how gender and body composition moderate the effects of an exercise and nutrition intervention module on body composition and fitness profiles in obese college students in China, addressing a growing health concern. Problem Statements: Obesity is on the rise among Chinese college students, necessitating effective intervention strategies. However, the impact of such interventions may vary based on gender and body composition, a knowledge gaps this study aims to fill. Methodology/Study Design: Quantitative research involved 337 college students from the Modern College of Humanities and Sciences, Shanxi Normal University, Linfen, China. Scales were used to assess fitness profiles, body image, exercise, nutrition intervention, and demographics. Data analysis utilised Partial Least Squares Structural Equation Modelling (PLS-SEM). Results/Findings: The exercise and diet intervention significantly improved body image and fitness profiles among obese college students. Notably, gender and body composition played crucial roles in moderating the intervention's effects on body image. Female participants experienced more substantial improvements in body image compared to males, with body composition also influencing the exercise-body image relationship. Implication/Significance: These findings have theoretical and practical implications. They enhance our understanding of exercise and diet interventions in reshaping body image and fitness profiles among obese college students. Importantly, they highlight the need for personalised interventions, considering gender and body composition. Policymakers and healthcare providers can use these insights to develop more effective programmes, to address the obesity issue among college students in China.